The big book of maker skills tools & techniques for building great tech projects - Hackett, Chris (Weldon Owen, 2014)
" ... Readers learn classic, tried-and-true techniques from the shop class of yore--how to use a metal lathe, or pick the perfect drill bit or saw--and get introduced to a whole new world of modern manufacturing technologies, like using CAD software, printing circuits, and more. Step-by-step illustrations, helpful diagrams, and exceptional photography make this book an easy-to-follow and easy-on-the-eyes guide to getting your project done."--Amazon.com.